An Experience in Distance Robotics Education through an Extension Course - Silva, Aline; Ferreira, Maria; Inácio, Flamarion; Andrade, Juliano (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
We deal in this article with the experience experienced with the elaboration of a fully EAD training course in robotics. We present the methodological proposal adopted using open source tools with the objective of reaching students and teachers of the public basic education network of a city in the state of Minas Gerais.